2015
DOI: 10.5152/akd.2014.5793
|View full text |Cite
|
Sign up to set email alerts
|

The evaluation of the clinical utility of urocortin 1 and adrenomedullin versus proBNP in systolic heart failure

Abstract: Objective:Urocortin 1 (UCN1) has vasodilator, diuretic, and natriuretic effects, and its expression increases in heart failure (HF). Adrenomedullin (ADM) increases cardiac output and lowers blood pressure in healthy men and in patients with heart failure. The aim of the study was to determine UCN1 and ADM levels in patients with HF, to evaluate the relationship of UCN1 and ADM with various clinical parameters, and to assess UCN1 and ADM as diagnostic markers in HF, in comparison with pro-brain natriuretic pept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…With regard to the blood levels of Ucns in cardiovascular diseases, we found numerous clinical studies that confirmed increased blood levels of Ucn1 and Ucn2 in a wide variety of cardiovascular diseases from hypertension to chronic HF, or from atrial fibrillation to aortic aneurysm 21 , 27 , 28 , 32 , 34 , 36 , 37 , 38 , 39 , 41 , 43 , 44 (Tables 1 and 2 ).…”
Section: Discussionmentioning
confidence: 83%
See 4 more Smart Citations
“…With regard to the blood levels of Ucns in cardiovascular diseases, we found numerous clinical studies that confirmed increased blood levels of Ucn1 and Ucn2 in a wide variety of cardiovascular diseases from hypertension to chronic HF, or from atrial fibrillation to aortic aneurysm 21 , 27 , 28 , 32 , 34 , 36 , 37 , 38 , 39 , 41 , 43 , 44 (Tables 1 and 2 ).…”
Section: Discussionmentioning
confidence: 83%
“…With regard to Ucn1, 12 studies measured the plasma levels in healthy volunteers 26 and in patient groups with various cardiovascular diseases, such as acute myocardial infarction (AMI; with or without controls) 27 or HF. 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 Seven studies reported significantly increased blood Ucn1 levels in cardiovascular diseases as compared with healthy controls (Table 1 ). 27 , 28 , 32 , 34 , 36 , 37 , 38 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations